open import Level module ordinal where open import zf open import Data.Nat renaming ( zero to Zero ; suc to Suc ; ℕ to Nat ; _⊔_ to _n⊔_ ) open import Data.Empty open import Relation.Binary.PropositionalEquality open import logic open import nat data OrdinalD {n : Level} : (lv : Nat) → Set n where Φ : (lv : Nat) → OrdinalD lv OSuc : (lv : Nat) → OrdinalD {n} lv → OrdinalD lv record Ordinal {n : Level} : Set n where constructor ordinal field lv : Nat ord : OrdinalD {n} lv data _d<_ {n : Level} : {lx ly : Nat} → OrdinalD {n} lx → OrdinalD {n} ly → Set n where Φ< : {lx : Nat} → {x : OrdinalD {n} lx} → Φ lx d< OSuc lx x s< : {lx : Nat} → {x y : OrdinalD {n} lx} → x d< y → OSuc lx x d< OSuc lx y open Ordinal _o<_ : {n : Level} ( x y : Ordinal ) → Set n _o<_ x y = (lv x < lv y ) ∨ ( ord x d< ord y ) s : {n : Level} → {lx : Nat} {x : OrdinalD {n} lx } { y : OrdinalD lx } → y d< x → x d< y → ⊥ trio<> {n} {lx} {.(OSuc lx _)} {.(OSuc lx _)} (s< s) (s< t) = trio<> s t trio<> {n} {lx} {.(OSuc lx _)} {.(Φ lx)} Φ< () d<→lv : {n : Level} {x y : Ordinal {n}} → ord x d< ord y → lv x ≡ lv y d<→lv Φ< = refl d<→lv (s< lt) = refl o<-subst : {n : Level } {Z X z x : Ordinal {n}} → Z o< X → Z ≡ z → X ≡ x → z o< x o<-subst df refl refl = df open import Data.Nat.Properties open import Data.Unit using ( ⊤ ) open import Relation.Nullary open import Relation.Binary open import Relation.Binary.Core o∅ : {n : Level} → Ordinal {n} o∅ = record { lv = Zero ; ord = Φ Zero } open import Relation.Binary.HeterogeneousEquality using (_≅_;refl) ordinal-cong : {n : Level} {x y : Ordinal {n}} → lv x ≡ lv y → ord x ≅ ord y → x ≡ y ordinal-cong refl refl = refl ≡→¬d< : {n : Level} → {lv : Nat} → {x : OrdinalD {n} lv } → x d< x → ⊥ ≡→¬d< {n} {lx} {OSuc lx y} (s< t) = ≡→¬d< t trio<≡ : {n : Level} → {lx : Nat} {x : OrdinalD {n} lx } { y : OrdinalD lx } → x ≡ y → x d< y → ⊥ trio<≡ refl = ≡→¬d< trio>≡ : {n : Level} → {lx : Nat} {x : OrdinalD {n} lx } { y : OrdinalD lx } → x ≡ y → y d< x → ⊥ trio>≡ refl = ≡→¬d< triOrdd : {n : Level} → {lx : Nat} → Trichotomous _≡_ ( _d<_ {n} {lx} {lx} ) triOrdd {_} {lv} (Φ lv) (Φ lv) = tri≈ ≡→¬d< refl ≡→¬d< triOrdd {_} {lv} (Φ lv) (OSuc lv y) = tri< Φ< (λ ()) ( λ lt → trio<> lt Φ< ) triOrdd {_} {lv} (OSuc lv x) (Φ lv) = tri> (λ lt → trio<> lt Φ<) (λ ()) Φ< triOrdd {_} {lv} (OSuc lv x) (OSuc lv y) with triOrdd x y triOrdd {_} {lv} (OSuc lv x) (OSuc lv y) | tri< a ¬b ¬c = tri< (s< a) (λ tx=ty → trio<≡ tx=ty (s< a) ) ( λ lt → trio<> lt (s< a) ) triOrdd {_} {lv} (OSuc lv x) (OSuc lv x) | tri≈ ¬a refl ¬c = tri≈ ≡→¬d< refl ≡→¬d< triOrdd {_} {lv} (OSuc lv x) (OSuc lv y) | tri> ¬a ¬b c = tri> ( λ lt → trio<> lt (s< c) ) (λ tx=ty → trio>≡ tx=ty (s< c) ) (s< c) osuc : {n : Level} ( x : Ordinal {n} ) → Ordinal {n} osuc record { lv = lx ; ord = ox } = record { lv = lx ; ord = OSuc lx ox } <-osuc : {n : Level} { x : Ordinal {n} } → x o< osuc x <-osuc {n} {record { lv = lx ; ord = Φ .lx }} = case2 Φ< <-osuc {n} {record { lv = lx ; ord = OSuc .lx ox }} = case2 ( s< s : {n : Level} → {x y : Ordinal {n} } → y o< x → x o< y → ⊥ o<> {n} {x} {y} (case1 x₁) (case1 x₂) = nat-<> x₁ x₂ o<> {n} {x} {y} (case1 x₁) (case2 x₂) = nat-≡< (sym (d<→lv x₂)) x₁ o<> {n} {x} {y} (case2 x₁) (case1 x₂) = nat-≡< (sym (d<→lv x₁)) x₂ o<> {n} {record { lv = lv₁ ; ord = .(OSuc lv₁ _) }} {record { lv = .lv₁ ; ord = .(Φ lv₁) }} (case2 Φ<) (case2 ()) o<> {n} {record { lv = lv₁ ; ord = .(OSuc lv₁ _) }} {record { lv = .lv₁ ; ord = .(OSuc lv₁ _) }} (case2 (s< y (case2 y x₂ x₁ osuc-< {n} {x} {y} y (case2 x ¬a ¬b c = tri> lemma1 (λ refl → ¬b (cong ( λ x → lv x ) refl ) ) (case1 c) where lemma1 : ¬ (Suc (lv a) ≤ lv b) ∨ (ord a d< ord b) lemma1 (case1 x) = ¬a x lemma1 (case2 x) = ⊥-elim (nat-≡< (sym ( d<→lv x )) c ) trio< a b | tri≈ ¬a refl ¬c with triOrdd ( ord a ) ( ord b ) trio< record { lv = .(lv b) ; ord = x } b | tri≈ ¬a refl ¬c | tri< a ¬b ¬c₁ = tri< (case2 a) (λ refl → ¬b (lemma1 refl )) lemma2 where lemma1 : (record { lv = _ ; ord = x }) ≡ b → x ≡ ord b lemma1 refl = refl lemma2 : ¬ (Suc (lv b) ≤ lv b) ∨ (ord b d< x) lemma2 (case1 x) = ¬a x lemma2 (case2 x) = trio<> x a trio< record { lv = .(lv b) ; ord = x } b | tri≈ ¬a refl ¬c | tri> ¬a₁ ¬b c = tri> lemma2 (λ refl → ¬b (lemma1 refl )) (case2 c) where lemma1 : (record { lv = _ ; ord = x }) ≡ b → x ≡ ord b lemma1 refl = refl lemma2 : ¬ (Suc (lv b) ≤ lv b) ∨ (x d< ord b) lemma2 (case1 x) = ¬a x lemma2 (case2 x) = trio<> x c trio< record { lv = .(lv b) ; ord = x } b | tri≈ ¬a refl ¬c | tri≈ ¬a₁ refl ¬c₁ = tri≈ lemma1 refl lemma1 where lemma1 : ¬ (Suc (lv b) ≤ lv b) ∨ (ord b d< ord b) lemma1 (case1 x) = ¬a x lemma1 (case2 x) = ≡→¬d< x open _∧_ TransFinite : {n m : Level} → { ψ : Ordinal {suc n} → Set m } → ( ∀ (lx : Nat ) → ( (x : Ordinal {suc n} ) → x o< ordinal lx (Φ lx) → ψ x ) → ψ ( record { lv = lx ; ord = Φ lx } ) ) → ( ∀ (lx : Nat ) → (x : OrdinalD lx ) → ( (y : Ordinal {suc n} ) → y o< ordinal lx (OSuc lx x) → ψ y ) → ψ ( record { lv = lx ; ord = OSuc lx x } ) ) → ∀ (x : Ordinal) → ψ x TransFinite {n} {m} {ψ} caseΦ caseOSuc x = proj1 (TransFinite1 (lv x) (ord x) ) where TransFinite1 : (lx : Nat) (ox : OrdinalD lx ) → ψ (ordinal lx ox) ∧ ( ( (x : Ordinal {suc n} ) → x o< ordinal lx ox → ψ x ) ) TransFinite1 Zero (Φ 0) = record { proj1 = caseΦ Zero lemma ; proj2 = lemma1 } where lemma : (x : Ordinal) → x o< ordinal Zero (Φ Zero) → ψ x lemma x (case1 ()) lemma x (case2 ()) lemma1 : (x : Ordinal) → x o< ordinal Zero (Φ Zero) → ψ x lemma1 x (case1 ()) lemma1 x (case2 ()) TransFinite1 (Suc lx) (Φ (Suc lx)) = record { proj1 = caseΦ (Suc lx) (λ x → lemma (lv x) (ord x)) ; proj2 = (λ x → lemma (lv x) (ord x)) } where lemma0 : (ly : Nat) (oy : OrdinalD ly ) → ordinal ly oy o< ordinal lx (Φ lx) → ψ (ordinal ly oy) lemma0 ly oy lt = proj2 ( TransFinite1 lx (Φ lx) ) (ordinal ly oy) lt lemma : (ly : Nat) (oy : OrdinalD ly ) → ordinal ly oy o< ordinal (Suc lx) (Φ (Suc lx)) → ψ (ordinal ly oy) lemma lx1 ox1 (case1 lt) with <-∨ lt lemma lx (Φ lx) (case1 lt) | case1 refl = proj1 ( TransFinite1 lx (Φ lx) ) lemma lx (Φ lx) (case1 lt) | case2 lt1 = lemma0 lx (Φ lx) (case1 lt1) lemma lx (OSuc lx ox1) (case1 lt) | case1 refl = caseOSuc lx ox1 lemma2 where lemma2 : (y : Ordinal) → (Suc (lv y) ≤ lx) ∨ (ord y d< OSuc lx ox1) → ψ y lemma2 y lt1 with osuc-≡< lt1 lemma2 y lt1 | case1 refl = lemma lx ox1 (case1 a